KINERJA PELAYANAN PERIJINAN PADA KANTOR PELAYANAN TERPADU (KTP) DI KABUPATEN GORONTALO - Alauddin . (Universitas Negeri Gorontalo, 2010)
Licensing service performance is one form of service that often gets complaints from the public so that the community demands for better services. In addition to long- winded bureaucratic chain, arrogant bureaucrats, not the professionals, ultimateTy money. Itś also no stranger to public service in the country when it imaged as a source of corruption. Thus, if the sting that should be public service in this cointry difficult to access by the poor, and becomes the trigger high-cost economy that ultimastely burden the macro economic performance, public burden, become embedded in our bureaucracy The results of this study indicate that the Licensing Service Performonce in lntegrated Services Ofice (OPT) Gorontalo regency on service disription Letter Business License (SIGU) can be said to be good, because almost all the indicators used in this study to asseess the performance of Licensing Services at the Office of Integrated services (oPT) Gorontalo regency, indicating satisfaction of tha servici user community. Contribulions and benefits that can be learned from this research is in the form of input for the Integrated Service Office (OpT) Gorontalo regency to be able to improve performance in holding licenses and permits, particularly in the service of non Permit Business Interruption (SIGU) in order to realize a quality service Keyword : Service Performance,quaIity, satisfoction